THE RELATIONSHIP OF MOTHER'S EDUCATION AND OCCUPATION TO THE EVENTS OF UNDERWEIGHT IN TODDLERS - Muhammad Iqbal; Jun Musnadi Is; Enda Silvia Putri (RADJA PUBLIKA, 2022)
Based on the 2019 SSGBI report, it was stated that the prevalence of underweight in toddlers, especially in Aceh province was 21.9%, West Aceh district was 24.5%. The high prevalence of underweight in Aceh Barat is certainly a public health problem that must be addressed so as not to adversely affect the quality of the nation's generation. Objective: to determine the relationship between education and mother's occupation on the incidence of underweight in toddlers in Kaway XVI sub-district. Methods: The design of this study was cross-sectional analytic. The population is mothers and toddlers aged 0-60 months in Kaway XVI sub-district. The number of respondents as many as 114 mothers and toddlers. The sample was selected using a purposive sampling technique. Data were collected using questionnaires and anthropometric measurements (BB/U) according to WHO standards. The data that has been collected were analyzed using univariate and bivariate analysis (chi-square test). Results: The results of the chi-square test showed that there was no significant relationship between mother’s education (p-value: 0.486; PR: 1.46; 95%CI: 0.492-4.433) and mother's occupation (p-value: 0.388; PR: 1.47; 95%CI : 0.561-4.396) to the incidence of underweight in toddlers.